Real-Time Continuous Glucose Monitoring Facilitates Feelings of Safety in Older Adults With Type 1 Diabetes: A Qualitative Study. (September 2017) - Litchman, Michelle L.; Allen, Nancy A.
Background: Older adults with long-standing type 1 diabetes (T1D) have a higher risk for hypoglycemia and hypoglycemia unawareness. Hypoglycemia can be dangerous, even fatal. Real-time continuous glucose monitoring (RT-CGM) effectively supports diabetes management and well-being in adult and pediatric populations. Little is known about older adults and RT-CGM use. The purpose of this study was to identify why RT-CGM was important for diabetes management in individuals with T1D 65 years of age. Methods: A convenience sample of older adults with T1D participated in one of two online surveys about RT-CGM. Categorical data were analyzed using descriptive statistics. A qualitative content analysis was conducted for open-ended responses. Results: Participants (N = 22) included in this study were those using RT-CGM (n = 11) and those who were not using RT-CGM, but desired to do so (n = 11). Those using RT-CGM were less likely to experience severe hypoglycemia ( P = .02) or hypoglycemia resulting in a fall or inability to operate a motor vehicle ( P = .01) Three major themes were identified: (1) RT-CGM facilitates feelings of safety by preventing hypoglycemia, (2) RT-CGM improves well-being, and (3) access is a barrier to RT-CGM use. Conclusions: RT-CGM improves safety and well-being in older adults with T1D by preventing hypoglycemia and associated injury and worry. Older adults without access to RT-CGM experience more severe hypoglycemia events that negatively affect their safety and well-being. Improving access to RT-CGM in older adults is critical to improving health and safety, and demands more attention from stakeholders in diabetes care.